JOB-POSITION RECOMMENDER SYSTEM USING KNOWLEDGE BASED RECOMMENDATION METHOD AT ATMI POLYTECHNIC SURAKARTA - Pratiwi, Dinita Christy; Atina, Vihi; Maulindar, Joni (Jurnal Teknik Informatika (Jutif), 2024)
ATMI Polytechnic Surakarta, one of the vocational colleges in Surakarta, currently has 152 employees and 13 managerial positions. The human resource management (HRM) unit has a strategy for selecting study program leaders and managers, but the procedure is still done by hand and is not based on standardized calculations. Therefore, a job-position recommender system is needed. This system aims to recommend candidates with the highest similarity score to the desired job criteria. The recommendation system was developed using the Knowledge-Based Recommendation method and the system development method employs a prototype. The stages included communication, quick planning, quick design modeling, prototype construction, and deployment, delivery and feedback. The calculation results show that an employee with the initials ADR has the highest similarity score for the job-position as head of the D3 Industrial Mechanical Engineering (TMI) study program with a score of 0.87. Therefore, this system can be used as a reference mechanism in building a job recommendation system at ATMI Polytechnic Surakarta.